El estrés laboral y su incidencia en la productividad de la cooperativa de ahorro y crédito Ambato LTDA. En las agencias de la provincia de Cotopaxi. - Castro Bonilla, Carlos David (2023)
Labor productivity in the business world is very transcendental, because it is a specific aspect from enterprise's profitability, but all part from staff, which operates in the environment, for this reason, the importance by knowing negative aspects, stressors, which it presents in the collaborators, that affect the efficient and effective performance an organization, since everything depends on performance and a good work environment. The current research project has as aim to analyze the existent relationship between work stress and the productivity in the Ambato Savings and Credit Cooperative Ltda in the agencies from Cotopaxi province, which it was used a quantitative approach study, through the process by collecting numerical data, with a descriptive, correlational design, likewise, it was applied the field and documentary (bibliographic) research type to know the relationship between the independent and dependent variable. Previously, it was applied the survey to the 47 collaborators, which consists 24 items for knowing the situation and real perception from cooperative's collaborators to fulfill the study aim. The results that shown this research based on the factors correlation and analysis found, what there is a mean positive correlation of Pearson's R reliability with 0.454 with a significance level 0.001%, which indicates that there is a stress labor incidence in productivity. This way, it was concluded, which stress and productivity are positively related, since this perspective, it is important to analyze these variables for business development, finally, in the proposal, it is set out to design improvement strategies, which allow developing the adequate performance staff and increasing the productivity.